Perancangan Poster Media Sosial Kampanye Penghematan Air - Desmond Christian Mauwa; Agus Danarto (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Clean water is a fundamental necessity with increasingly limited availability due to unwise household consumption. Although research on water crises is extensive, engaging educational visual communication media to build public awareness remains scarce. This research aims to design informative visual communication media in the form of Instagram posters as a tool for water conservation education among teenagers. The method employed is qualitative descriptive, adapting Robin Landa's "Design Method," which encompasses five stages from orientation to implementation. Data were collected through questionnaires with 24 Generation Z respondents in Jabodetabek, observations, and literature reviews, analyzed using SWOT and the 5A Funnel. Research findings reveal that while 58.3% of respondents understand the concept of water efficiency, 62.5% are not yet consistent in daily application. In response, the “Cermat Pakai Air” campaign was designed, consisting of 14 infographic posters. The results demonstrate that contemporary visual design approaches are effective in increasing awareness and interest in water-saving actions among the target audience. Theoretically, this research implies that harmonious visual elements can bridge environmental information gaps for Generation Z. Practically, this campaign strategy can be adopted by relevant institutions to encourage behavioral changes in maintaining water security through social media platforms.